Polarization reversal and memory effect in anti-ferroelectric materials. (February 2017) - Vopson, Melvin M.; Caruntu, G.; Tan, Xiaoli
Abstract: A solid-state memory effect is defined as the ability of a material to store information, and it requires at least two switchable memory states that can be addressed by an externally controlled parameter. In this article we present experimental evidence of a memory effect in anti-ferroelectric Pb0.99 Nb0.02 [(Zr0.57 Sn0.43 )0.94 Ti0.06 ]0.98 O3 polycrystalline ceramic materials. This study indicates that anti-ferroelectrics encode data in their ferroelectric sublattices, resulting in a 4-state memory capable of storing 2 digital bits simultaneously. This result opens up the possibility of realizing non-volatile anti-ferroelectric random access memory, as well as other possible devices and logic applications based on anti-ferroelectric materials. Graphical abstract: